THE CHALLENGE OF THE EMERGENCY REMOTE TEACHING IN THE EDUCATION OF ART CONSERVATORS. EXPERIENCES AND REFLECTIONS - Alexopoulou, Athena (Design/Arts/Culture, 2022)
COVID-19 pandemic and the measures to constrain it have influenced, among others, every dimension of the cultural heritage; from research, conservation and preservation projects to training and education. The closure of training buildings and campuses, the cancellation of face-to-face classes and labs and other learning experiences forced a shift to emergency remote teaching. Especially, for art conservators education, as the field of heritage conservation is powered by art history, technology and science, any deceleration has an important impact on it. Moreover, conservators have to be in contact with the real object, to be present physically in the archaeological sites, to interact with the material of the monuments and traditionally they work very close to them. The closure of the education domain deprived conservation students from the physical contact with the objects, but had fostered the digital transformation of the heritage sector, as well as the academic conservation education. The goal of this paper is to discuss advantages and weaknesses of emergency remote teaching comparing to face-to-face teaching and online teaching too, as well as to record the experience of the remote teaching in the Department of Conservation of Antiquities and Artworks and the opportunities emerged for the curricula of the Department.